(Recovering) China’s Urban Rivers as Public Space - Kelly Shannon; Chen Yiyong (Footprint)
This article focuses on the revered role rivers in China once held – in cartography, history, mythology, festivals, cities, and everyday life. It reviews and summarizes ‘hydraulic civilization’, taking cognizance of feng shui as it does so. Four historical cases testify to the fact that China’s great cities were founded on riverbanks and developed in tandem with floodplain dynamics.